Anti-phytopathogen, multi-target acetylcholinesterase inhibitory and antioxidant activities of metabolites from endophytic Chaetomium globosum. Issue 22 (16th November 2016) - Li, Wei; Yang, Xueqiong; Yang, Yabin; Duang, Rongting; Chen, Guangyi; Li, Xiaozhan; Li, Qiling; Qin, Shaohuan; Li, Shuquan; Zhao, Lixing; Ding, Zhongtao
Abstract: Fourteen metabolites with various structure types were isolated from endophytic Chaetomium globosum . Five compounds were separated from genus Chaetomium for the first time. Some compounds exhibited remarkable inhibition against phytopathogenic fungi causing root rot of Panax notoginseng. Compounds1 –5 had significant DPPH-free radical-scavenging activity. Compounds3 and5 indicated significant inhibitions against the acetylcholinesterase (AChE). From preliminary structure–activity relationship, it was found that the oxygenic five-membered ring of3 and5 was crucial in the anti- AChE activity. These structures provide new templates for the potential treatment and management of plant diseases and Alzheimer disease. Abstract :